2014
DOI: 10.1016/j.margen.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity and photic plasticity of myosin gene transcription in fast skeletal muscle of Atlantic cod (Gadus morhua)

Abstract: Circadian rhythmicity and photic plasticity of myosin gene transcription in fast skeletal muscle of Atlantic cod (Gadus morhua

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(44 reference statements)
2
11
1
Order By: Relevance
“…We have not investigated if the muscle cells express photopigments such as melanopsins in culture but we have previously reported that cryptochromes, a group of genes coding for photosensitive proteins, are expressed in Atlantic cod skeletal muscle [16]. Further, we cannot conclusively exclude light as a synchronization factor in Atlantic cod skeletal muscle, since the present study and previous reports suggest that this tissue is responsive to changes in lighting regimes [15,16,17,19].…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…We have not investigated if the muscle cells express photopigments such as melanopsins in culture but we have previously reported that cryptochromes, a group of genes coding for photosensitive proteins, are expressed in Atlantic cod skeletal muscle [16]. Further, we cannot conclusively exclude light as a synchronization factor in Atlantic cod skeletal muscle, since the present study and previous reports suggest that this tissue is responsive to changes in lighting regimes [15,16,17,19].…”
Section: Discussioncontrasting
confidence: 59%
“…The rhythmic expression of several clock genes in fast skeletal muscle of Atlantic cod suggests the presence of a peripheral clock in this tissue [15,16]. In the present study, we developed in vitro (myosatellite cell culture) and ex vivo (muscle explant) models of muscle growth to ascertain its autonomy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations